The Development of an Online Instrument for Prior Learning Assessment and Recognition of Internationally Educated Nurses: A Pilot Study - Santa Mina, Elaine Elizabeth; Eifert, Carol; Ireland, Martha; Fine, Carol; Wilson, Gail; Micevski, Vaska; Wojtiuk, Ruth; Valderrama, Martha (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
A fully online prior learning assessment and recognition (PLAR) tool for internationally educated nurses (IENs) was developed and tested by an inter-professional team at Ryerson University. The tool consisted of two stages: a self-assessment component followed by a multiple-choice examination and narrative (vignette) evaluation. The purposes of the study were to describe the demographic profile of the IEN registered nurse (RN), to develop the benchmark responses that demonstrate competency at the entry-to-practice level of the typical IEN RN, and to describe the experience of completing an online PLAR tool. A mixed-method approach was used. Findings demonstrated that IEN RNs who immigrate to Ontario, Canada, are of various ages and come from a wide spectrum of countries. The PLAR process holds promise for an objective assessment of IEN’s eligibility to write the Canadian Registered Nurses Examination (CRNE) and to meet a global need. Further testing of the tool across a broader sample is required.